The Influence of School Literacy Programs on Students' Reading Ability in Elementary Schools - Ribka Setiani; Resnita Dewi; Anastasia Baan (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Literacy applied in elementary schools is very important because it is the main foundation for the development of children's knowledge and skills in the future. Good literacy will help students understand other lessons. To develop literacy in schools, a culture of literacy is instilled in students, and learning resources are provided. The low literacy rate is due to a lack of understanding of the concept of basic literacy and the implementation of literacy that is less supportive. In addition, there is a gap in access and quality of education between urban and rural areas. In some remote areas, children have less access to reading books and minimal libraries, resulting in low interest in reading for students. The low interest in reading for students will have an impact on their reading ability. The existence of libraries and reading corners in schools is a school literacy program that can be carried out to develop students' reading skills. The purpose of this study was to determine the effect of school literacy programs on students' reading skills. This study is a descriptive qualitative study with observation and interview methods. Data Analysis Techniques are through the stages of reduction, display, and conclusion/verification. The research sample can be determined from related data sources, from interviews and observations of students from grade IV, such as class teachers, librarians, and other data sources. The results of this study indicate that this study with the title found that literacy in the scope of students at SD Negeri 7 Buntao is still low, so it is necessary to increase literacy in the scope of the school. This study is useful for other schools that want to carry out literacy programs.